Psychological and Behavioural Determinants of Problematic Mobile Phone Use in Female Health Science Undergraduate - Julianti Jauhari (Asian Journal of Public Health and Nursing, 2025)
Background: Problematic smartphone use (PSU) represents a growing public health challenge, particularly among future healthcare professionals who require high levels of focus and digital literacy. This study aims to investigate the psychosocial and lifestyle determinants of PSU among female health science undergraduate students. Methods:A large-scale cross-sectional study was conducted with 1,570 female students in Aceh, Indonesia. Participants were assessed using validated instruments: the Mobile Phone Problem Use Scale – Short Version (MPPUS-16), Mobile Attachment Questionnaire (MAQ), Peer Influence Scale, and Rosenberg Self-Esteem Scale (RSES). Data were analyzed using non-parametric bivariate tests and multiple linear regression with robust standard errors to identify independent predictors. Results:The mean PSU score was 36.5 (SD = 9.1). In the multivariable model, peer influence (β = -0.175, p < 0.001) emerged as the strongest predictor of PSU, followed by mobile attachment (β = 0.159, p < 0.001). While self-esteem and body mass index (BMI) showed significant but modest associations, lifestyle factors played a distinct role; students who never exercised reported significantly higher PSU scores (p = 0.0009). The model accounted for 8.1% of the total variance. Conclusions:PSU among female health science students is primarily driven by interpersonal dynamics and emotional device reliance rather than financial resources. These findings suggest that digital well-being interventions for future health professionals should move beyond individual psychological traits to address peer-driven digital behaviors and promote lifestyle balance.